Isolation, molecular identification, and phylogenetic analysis of infectious bronchitis virus from commercial chicken farms in Mekele and Bishoftu, Ethiopia, 2023–2024 - Nigusu Berhanu; Eyob Hirpa; Hawa Mohammed; Abinet Legesse; Getaw Deresse; Eyob Assefa; Takele Tesgera; Mirtneh Akalu; Takele Abayneh; Berecha Bayissa; Liyuwork Tesfaw; Kenaw Birhanu; et al. (Virology Journal)
Abstract Background Avian infectious bronchitis (IB) is a highly contagious respiratory disease that affects the poultry industry globally. The disease is caused by avian infectious bronchitis virus (IBV), member of the genus Gammacoronavirus. In Ethiopia, IBV has been reported in both commercial and backyard chickens based on clinical observation. The objectives of this study were to isolate the virus, conduct molecular based identification, and phylogenetic analysis of the circulating IBV isolates. Methods and materials A cross-sectional study was conducted between November 2023 and May 2024 in Mekele and Bishoftu, Ethiopia. A total of 49 clinical samples were collected, comprising 12 tissue samples and 39 pooled swab samples. Of these, 6 samples—specifically, 5 swab samples and 1 tissue sample—tested positive for infectious bronchitis virus (IBV) through virus-specific conventional RT-PCR and real-time PCR. Nested PCR was performed using serotype-specific primers. The purified PCR products, which targeted the spike glycoprotein S1 subunit gene and the 3′ UTR of the IBV, were sequenced, followed by phylogenetic tree analysis. Results The six positive samples propagated into specific pathogen free embryonated eggs and exhibited characteristic IBV lesions and mortality observed over five consecutive passages. IBV isolates from Bishoftu (n = 4) and Mekele (n = 2) were amplified using one-step RT-PCR to target 466 bp of the S1 subunit gene and 433 bp of the 3ʹUTR. A BLAST search on the S1 partial gene and 3ʹUTR sequences, nested PCR, and phylogenetic analysis revealed that the present IBV isolates are genetically similar to the Massachusetts serotype. The S1 gene sequences of the five IBV isolates were deposited in GenBank with accession numbers PQ389500 to PQ389504. Conclusions This is the first detailed study on IB virus isolation, molecular detection, sequencing, and phylogenetic analysis in Ethiopia. The findings revealed that the outbreaks were caused by the IB virus, which created a serious health risk and economic losses in the chicken industry. To the author’s knowledge, this is the first comprehensive study on the isolation and genetic analysis of IBV in Ethiopia. Further research on the economic impact of IBV in chicken production, farm biosecurity, serotyping of circulating IB virus, and vaccine development based on the local serotypes is recommended.